Architektur als Akteur. Eine Soziologie der Architekturerfahrung. - Leuenberger, Theresia (My University, 2018)
Die Arbeit untersucht Architekturerfahrungen aus der Perspektive der Nutzer und Nutzerinnen. Es fehlen bislang theoretische Grundlagen, um Architekturerfahrungen sozial differenziert zu untersuchen und zu definieren. Diese Arbeit füllt eine Forschungslücke, indem sie die Raumsoziologie mit der Theorie sozialer Praxis sowie dem Instrumentarium der Akteur-Netzwerk-Theorie kombiniert und Architekturerfahrungen relational, prozesshaft und praxeologisch bestimmt. Die Autorin erhebt die empirischen Grundlagen mittels des Gruppendiskussionsverfahrens mit je drei Gruppen Jugendlicher unterschiedlicher Ausbildungsrichtungen im Kunsthaus Bregenz und in der Kunsthal Rotterdam. Die Analyse der Gespräche anhand der dokumentarischen Methode ermöglicht es, sowohl verschiedene Architekturerfahrungen als auch die Architekturerfahrungsprozesse der einzelnen Gruppen zu bestimmen. Zentrales Ergebnis der Arbeit ist, dass Architekturerfahrungen sich nach der Etablierung einer spezifischen Sozialität, in Abhängigkeit vom rationalen oder affektiven mentalen Gehalt der Erfahrung und der Art der Prägung, unterscheiden: Zeichnet die materielle Struktur des Gebäudes die Erfahrung vor, so ist die Zahl derjenigen, die es auf ähnliche Weise erfahren, größer, als wenn die Erfahrung vom spezifischen Wissensbestand des Einzelnen abhängt. Ein hoher Grad an beruflicher Sozialisation und die Bezugnahme auf das eigene Wissen schränken den Erfahrungsspielraum eher ein, während der Verzicht auf oder die Unterdrückung des eigenen Wissens unerwartete Erfahrungen begünstigt. Erkenntnisse dieser Art ermöglicht es den Planern und Planerinnen, bereits in der Entwurfsphase eine Einschätzung darüber vorzunehmen, in welchem Maß die von ihnen getroffenen Annahmen von den zukünftigen Nutzern und Nutzerinnen der Gebäude geteilt werden.

The aim of the Architecture as an Actor study is to elucidate how users experience architecture. Within the context of history and theory of architecture, manifold architecture experiences are discussed, while presuming their general validity. In particular, a theoretical basis for a socially differentiated research and a definition of architecture experiences are presently lacking. By combining the sociology of space with the theory of social practice and the terminology of the actor-network theory, in this work, architecture experiences are conceived as relational as a process and as a practice. The study is thus guided by the premise that the perspective of the perceiver as well as the material structure of the building have an impact on the architecture experience. The author collected the empirical data in the Kunsthaus Bregenz and Kunsthal Rotterdam through three group discussions in each building with young people from different educational backgrounds. Based on the documentary analysis, various architecture experiences and the processes of architecture experience of each group are identified. Architecture experiences differ analytically depending on how elements of a building (arrangement) are linked (synthesis) from a certain point of view while perceiving, passing through or using it (spacing). A key result of the study thus pertains to the revelation that architecture experiences are distinguished according to the produced sociality, according to their rational or affective mental dimension and the corresponding impact. For example, when the material structure of the building prescribes the experience, it is shared by more individuals, than if the experience is shaped by the specific knowledge of the observer. Relying largely on acquired knowledge tends to limit the number of ways in which architecture is experienced and at the same time diminishes the openness that is required to make unexpected experiences. For the social studies, the definitions and findings provide a model that demonstrates how the concept of experience is applied to architecture and allow planners to estimate whether the assumptions made during the design phase will apply to the end-user. With the conception and definition of architecture experiences based on the empirical research with a theoretical basis, this dissertation provides instruments for further research into similar and related questions, as well as a proposal for a sociology of architecture experience.
Architecture as an actor. A sociology of architectural experience.
Keywords: Stadtsoziologie; Architektur; Architektursoziologie; Gebäude; Wahrnehmung; Erfahrung; Gebäudeplanung; Stadtgestaltung; Städtebau; Wohnen; Wahrnehmung; Jugendlicher; Sozialisation; Empirische Untersuchung; Raumsoziologie